Studi Interpretatif Terhadap Makna dan Nilai Pendidikan Dalam Lagu Sayang Api Coa Sayang dari Rejang Lebong: Penelitian - Silvi Ulandari; Robbyferdian (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to uncover the meaning and educational values of the Rejang Lebong folk song "Sayang Api Coa Sayang" through an interpretive approach. This song not only represents aesthetic expression, but also conveys moral messages and character education, especially those related to environmental awareness, social responsibility, and the preservation of local culture. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that this song is rich in educational values such as love for the environment, respect for ancestors, social empathy, and cultural preservation. This song can be used as a medium for character education in the context of local wisdom-based learning.